Cell manufacturing for cell-based tissue engineering: a focus on vascularized, skeletal muscle regeneration - de Medeiros Cartaxo Esmeraldo, Bruno; Laurence, Keely A.; Kwee, Brian J. (Frontiers in Chemical Engineering, 2025)
Cell manufacturing processes play a crucial role in cell-based tissue engineering by isolating, purifying, culturing, expanding, modifying, cryopreserving, and formulating patient-derived cells in vitro before utilizing them for tissue regeneration. Currently, researchers apply various methods for cell manufacturing, including bioreactors, defined chemical cues, and substrate modifications. However, factors such as loss of cell potency and heterogeneity are critical challenges when engineering tissues for regenerative medicine. In particular, neglecting cellular heterogeneity during cell expansion prevents the formation of tissues that recapitulate the structural and cellular heterogeneity of our native tissues. This review discusses current and emerging approaches for cell manufacturing, with a focus on biomanufacturing for vascularized, skeletal muscle tissue engineering. Specifically, this review highlights 1) the U.S. Food and Drug Administration’s regulation of manufacturing for cell therapies, 2) state-of-the-art approaches for manufacturing endothelial cells and muscle stem cells that maintain cellular identity and potency, and 3) emerging tools and methods for measuring and manipulating cellular heterogeneities. Ultimately, these approaches can be leveraged to manufacture and formulate tissue-engineered products that mimic the heterogeneous form and function of our native tissues.